The Supercarbonate Apatite-MicroRNA Complex Inhibits Dextran Sodium Sulfate-Induced Colitis - Tadafumi Fukata (Molecular Therapy: Nucleic Acids, 2018)
The incidence of inflammatory bowel disease (IBD) is increasing. Nucleic acid-based medicine has potential as a next-generation treatment, but it is rarely successful with IBD. The aim of this study was to establish a microRNA-based therapy in an IBD model. For this purpose, we used microRNA-29 (miR-29) and a supercarbonate apatite (sCA) nanoparticle as a drug delivery system. Injection of sCA-miR-29a-3p or sCA-miR-29b-3p into mouse tail veins markedly prevented and restored inflammation because of dextran sulfate sodium (DSS)-induced colitis. RNA sequencing analysis revealed that miR-29a and miR-29b could inhibit the interferon-associated inflammatory cascade. Subcutaneous injection of sCA-miR-29b also potently inhibited inflammation, and it efficiently targeted CD11c+ dendritic cells (DCs) among various types of immune cells in the inflamed mucosa. RT-PCR analysis indicated that the miR-29 RNAs in CD11c+ DCs suppressed the production of interleukin-6 (IL-6), transforming growth factor β (TGF-β), and IL-23 subunits in DSS-treated mice. This may inhibit Th17 differentiation and subsequent activation, which is critical in IBD pathogenesis. In vivo experiments using a non-natural artificial microRNA sequence revealed that targeting of DCs in the inflamed colon is an exceptional feature of sCA. This study suggests that sCA-miR-29s may open a new avenue in nucleic acid-based medicine for IBD treatment. Keywords: microRNA-29a, microRNA-29b, DSS colitis, supercarbonate apatite, dendritic cells